RPP Development Management in Improving the Teaching and Learning Process at SDN Sukamulya III - Ujang Cepi Barlian; Fitriah Yuliasari; Nia Kurniawati (al-Afkar, Journal For Islamic Studies, 2023)
RPP development management (Learning Implementation Plan) is an important aspect in improving the teaching and learning process in schools. RPP is a document that explains in detail the material to be taught, learning objectives, activities to be carried out, and evaluation to be carried out. Effective lesson plan development management can assist teachers in managing teaching and learning processes more effectively, improve student learning outcomes, and improve the quality of teaching and learning processes in schools. This study aims to find out how lesson plan development management can improve the teaching and learning process at SDN Sukamulya III. This study uses a qualitative approach by collecting data through interviews, observation, and documentation. The results of the study show that effective management of RPP development can improve the teaching and learning process at SDN Sukamulya III by: (1) compiling lesson plans according to the curriculum and competency standards, (2) compiling lesson plans that refer to students' needs and interests, (3) preparing lesson plans that refer to the principles of effective learning, (4) integrating various learning resources in lesson plans, and (5) evaluating the processes and results of student learning continuously.